Activités rituelles autour d’une source entre la France et l’Espagne (vie s. av. J.-C.-vie s. apr. J.-C.) : la Fajouse à Argelès-sur-Mer (Pyrénées-Orientales) - Ingrid Dunyach (Gallia)
The site of la Fajouse is situated in the Roussillon, Dept of Pyrénées-Orientales, at the frontier between France and Spain. It was recently discovered at the top of the massif des Albères, on the Pyrénées’ eastern limit Mediterranean sea and the Greek colonies of Rhode and Emporion. Brought to light between 2012 and 2014, the remains allowed to put in evidence cult activities around a source from the 6th century BC. However the most densely occupied period is situated at the end of the 4th century and during the 3rd century BC, period when the source and buildings below have been laid out. A change in the ritual practices has been noticed at the very end of the 3rd and 2nd centuries – at the time of the Roman establishment in Spain – from which the site becomes sporadically frequented during the Roman period until the 4th century AD or even the 6th century, before being sunk into oblivion. Being remote from any town it allows to provide data on the sacred areas, called cult sites on the fringes. The examination of the site highlights practices being performed as well as territory dynamics of the populations in the heart of Mediterranean cultural contacts.